Charles P. Kindleberger, Centralization versus Pluralism. A Historical Examination of Political-Economic Struggles and Swings within Som Leading Nations, København: Handelshøjskolens Forlag, 1996, 102 s., kr. 175,00. - Amstrup, Niels (Politica, 1996)
-